Edukasi Serta Pendampingan Budidaya Cacing ANC Dan Produksi Pelet Industri Rumahan Di Desa Wonosari Kabupaten Deli Serdang - Ilham Mubaraq Ritonga; Azwansyah Habibie; Dody Hidayat (Jurnal TUNAS, 2022)
This Educational and Assistance activity for ANC Worm Cultivation and Home Industry Pellet Production is a Community Partnership Program activity involving partners, namely the Deli Serdang Worm Farmers Association (ATC Deli Serdang) located in Wonosari Village, Tanjung Morawa District, Deli Serdang Regency. Priority issues related to production processes, financial management, not yet producing downstream products that are attractive to the market, and marketing processes. The learning and mentoring method provide solutions: (1) Increasing the production of ANC Worms in new ways and using technology with the "Worm Drying Oven" machine to produce pellets with a very fast drying process (2) Pellet Grinding and Printing Machines with this method Screw Press the process of making pellets will be better and faster, (3) Provide the technology of using Hand Sealer so that the packaging and labels look much more attractive/eye-catching. (4) Utilization of social media as a means of product promotion in market expansion, (5) Providing Financial Report Preparation Training to all members of farmer groups in accordance with Accounting principles (Financial Accounting Standards – Micro, Small, and Medium Entities).